2021
DOI: 10.18805/ijar.bf-1417
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Qualitative Characteristics and Their Use to Distinguish the Origin of the Bali Cattle Population

Abstract: Background: The development of local Bali cattle in ex-situ areas allow for the formation of new qualitative phenotypic characteristics. The aim of this study is to characterize Bali cattle that have been created in Jambi Province’s ex-situ environment in several of rearing areas. Methods: A research sample of 478 Bali cattle from Muaro Jambi (MJB) district, Sarolangun (SLG) district, Tanjung Jabung Timur (TJT) District, Jambi City (KJB) and PTPN VI were surveyed. The qualitative phenotype characteristic obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This means that SC and BC sheep cannot be distinguished based on cluster analysis and this is in accordance with the results of the analysis of variance which found that almost all the body sizes of the two sheep were not significantly different. By using discriminant analysis, Dauda et al [22] can differentiate between several breed sheep in Nigeria, and Hayanti et al [23] can also distinguish the origin of Bali cattle in the Jambi province of Indonesia. Discriminant analisys can also as a tool to identify bovine and ovine meat produced from pasture or stall-fed animals [24].…”
Section: Resultsmentioning
confidence: 99%
“…This means that SC and BC sheep cannot be distinguished based on cluster analysis and this is in accordance with the results of the analysis of variance which found that almost all the body sizes of the two sheep were not significantly different. By using discriminant analysis, Dauda et al [22] can differentiate between several breed sheep in Nigeria, and Hayanti et al [23] can also distinguish the origin of Bali cattle in the Jambi province of Indonesia. Discriminant analisys can also as a tool to identify bovine and ovine meat produced from pasture or stall-fed animals [24].…”
Section: Resultsmentioning
confidence: 99%
“…If two categories show high coordinates and are close together in space, the categories tend to be related. If two categories are seen at high coordinates but are not close together (with opposite signs), the variables tend to be inversely associated (Di Franco, 2016;Hayanti et al, 2022). Discrimination measures on dimensions 1 and 2 will build a plot of the relationship between categories presented in In JTT, Priangan and Garut sheep, the distribution of body qualitative morphological characteristics is diverse and close to each other.…”
Section: Typology Of Qualitative Morphological Characteristicsmentioning
confidence: 99%
“…This knowledge can be used to develop breeding programs aimed at improving specific traits or creating new breeds with desirable characteristics (17). Morphometric studies can be used to study the genetic diversity of a breed (20,35,10,4) breed types and functions (30,8,21), prediction of body weight and carcass (3,12), prediction of daily milk production (33,27,21), udder health (31,33), embryo growth (19), differentiation and estimation of genetic distance between populations/breeds (25,7) and differentiation based on origin (18) are as well as giving recommendations for genetic improvement and management of livestock genetic resources in the context of conservation (23). The diversity of livestock breeds can also be estimated based on genetic diversity, both in gene regions associated with certain traits (2,13) and non-gene regions/microsatellite markers (16).…”
Section: Introductionmentioning
confidence: 99%